2020
DOI: 10.3390/molecules25215108
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Study of Metallacycles Formed by Pyrazolate Ligands and the Coinage Metals M = Cu(I), Ag(I) and Au(I): (pzM)n for n = 2, 3, 4, 5 and 6. Comparison with Structures Reported in the Cambridge Crystallographic Data Center (CCDC)

Abstract: The structures reported in the Cambridge Structural Database (CSD) for neutral metallacycles formed by coinage metals in their valence (I) (cations) and pyrazolate anions were examined. Depending on the metal, dimers and trimers are the most common but some larger rings have also been reported, although some of the larger structures are not devoid of ambiguity. M06-2x calculations were carried out on simplified structures (without C-substituents on the pyrazolate rings) in order to facilitate a comparison with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…Many cyclic trinuclear pyrazolato Copper(I) complexes, with the notable exception of [Cu(μ-L5pz)]3, have intermolecular cuprophilic interactions between each trinuclear plane and Cu•••Cu distances ranging in length from 2.9099(4) to 4.3155 Å [28][29][30]. Similar metallophilic interactions have been observed in other trinuclear complexes of group 11 metal (I) ions [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Many cyclic trinuclear pyrazolato Copper(I) complexes, with the notable exception of [Cu(μ-L5pz)]3, have intermolecular cuprophilic interactions between each trinuclear plane and Cu•••Cu distances ranging in length from 2.9099(4) to 4.3155 Å [28][29][30]. Similar metallophilic interactions have been observed in other trinuclear complexes of group 11 metal (I) ions [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 70%
“…Cyclic trinuclear complexes with group 11 metal(I) ions have been of interest to coordination chemists for three decades [1][2][3][4]. One of the ligands known to form these cyclic trinuclear complexes is pyrazolate, which is a bridging ligand that coordinates many transition metal ions in a Npz-M-Npz linear mode (Npz = pyrazolyl nitrogen atom) [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclic trinuclear complexes with monovalent coinage metal ions have been of interest to coordination chemists for three decades [ 1 , 2 , 3 ]. One of the ligands known to form these cyclic trinuclear complexes is pyrazolate [ 4 , 5 , 6 ], which is known to act as an A-frame-like bridging ligand with some metal ions, with an Npz–M–Npz linear coordination mode (pz = pyrazolate anion, C 3 H 3 N 2 − ) [ 1 , 2 , 3 , 4 , 6 , 7 , 8 , 9 ]. Early studies in 1970 suggested that silver(I) pyrazolato complexes existed as a polymeric 1-D chain [Ag(pz)] n ( Figure 1 , left) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Elguero and Alkorta reported a computational study of metallacycles formed by pyrazolate ligands and the coinage metals (pzM) n for n = 2, 3, 4, 5 and 6 and carried out a comparison with structures reported in the Cambridge Crystallographic Data Center (CCDC). They discussed the most common size of the metallacycles’ ring depending on the metal and analyzed the stability of different ring sizes [ 1 ]. By using an unexpected synthetic method, Leznoff and Fusijawa et al obtained and characterized a silver(I) pyrazolate complex [Ag(µ-L1Clpz)] n as a coordination polymer, thus broadening the family of silver(I) coordination polymers [ 2 ].…”
mentioning
confidence: 99%